Business strategy development to enhance fintech peer-to-peer lending industry in indonesia - Ananta Sudirman, Friyanti; Sidik Motik, Surani (The Indonesian Journal of Business Administration, 2019)
Abstract. Fintech P2P lending industry is still be an attractive industry in the past 3 years in Indonesia. Despite the decreasing growth in 2017, new start-up in P2P lending industry start to increase again in 2018. The P2P companies face lots of opportunities, challenges and follow with the multiple risk in running the business. How to develop the company strategy to be able to sustain the business in the future will be a focus to all the stakeholder in the industry. The aim of this research are to discuss the business strategy development, how the external and internal environment affect the Industry and and how the strategy to enhance the P2P lending industry in Indonesia. The methodology of the research is qualitative approach where the data collected through interview with the expert and observation to analyse the industry internal and external aspect as well as the stakeholeder analysis. The sustainable industry related with how the companies comply to the regulation, thus the paper scope is limited to the registered companies. The synergize between different systems, different technology has not to be a burden on the collaboration among the stakeholder. Collaboration as the key to promote the industry as well as the regulation development be a major key forced to the industry. P2P companies need to shield the organization with risk management internally as well as externally.The strategist needs to look beyond shareholders and apply a stakeholder perspective to ensure long-term survival and success of the firm. A firm that does not respond to stakeholders beyond stockholders in a way that keeps them committed to its vision will not be successful.  Keywords:  business strategy, fintech, collaboration, peer-to-peer lending, sustainable ecosystem